Device of identification of parameters and currents of the rotor three-phase asynchronous motor - A. J. Afanasiev; V. G. Makarov; Y. A. Yakovlev; V. N. Khannanova (Известия высших учебных заведений: Проблемы энергетики)
For identification of parameters of the asynchronous three-phase motor and its loading it is necessary to have information on currents of a short-circuited rotor. On the basis of a continuous gradient method of search of a minimum of certain and positive function from not knittings of the equations of the generalized electrical machine the method of identification of parameters of the asynchronous three-phase motor and currents of a short-circuited rotor is developed. The function chart of the device of identification is developed. Possibility of realization of this device with use of simple elements, such as multipliers, adders and integrators is shown.